upaya guru dalam menanamkan nilai-nilai keislaman pada anak usia dini di RA Al Ukhuwah - alawiah, tutialawiah (Hamka Ilmu Pendidikan Islam, 2025)
This study aims to determine the efforts of teachers in instilling Islamic values ​​in early childhood at Raudhatul Athfal (RA). Instilling Islamic values ​​from an early age is very important as a basis for the formation of children's character and morals. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation of teachers and learning activities at RA. The results of the study indicate that teachers' efforts in instilling Islamic values ​​are carried out through habituation of religious activities, such as daily prayer, worship practices, exemplary attitudes, Islamic story-based learning, and the integration of Islamic values ​​in learning and play activities. Supporting factors in the implementation of these efforts include the active role of teachers, school environmental support, and parental involvement, while inhibiting factors include differences in children's characters and limited learning time. Thus, teachers' efforts have a very important role in instilling Islamic values ​​in early childhood as a provision for children's moral and spiritual development in the future.